2022
DOI: 10.1186/s13019-022-01983-8
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted pulmonary lobectomy with lung cancer in a patient with situs inversus totalis

Abstract: Background Situs inversus totalis (SIT) is a relatively rare congenital abnormality in which the major thoracic and abdominal visceral organs are reversed from their usual positions. In patients with SIT and bronchial carcinoma, surgical difficulty increases sharply. It has been reported that the video-assisted thoracic surgery (VATS) still poses the operator to a challenge situation. The similarity of surgical positions and the flexibility of the mechanical arm in robotic surgery, may be benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This lady was the first patient to undergo a robotic-assisted lobectomy in Jordan. According to Yang et al, robotic-assisted thoracic surgery was advantageous in a case of lobectomy in a cancer patient with situs inversus totalis as it helped in identifying the anatomical abnormalities and facilitated the surgery [7]. In addition, Nomori et al concluded that a largely fused fissure is not a limiting factor for the performance of VATS lobectomy [8].…”
Section: Discussionmentioning
confidence: 99%
“…This lady was the first patient to undergo a robotic-assisted lobectomy in Jordan. According to Yang et al, robotic-assisted thoracic surgery was advantageous in a case of lobectomy in a cancer patient with situs inversus totalis as it helped in identifying the anatomical abnormalities and facilitated the surgery [7]. In addition, Nomori et al concluded that a largely fused fissure is not a limiting factor for the performance of VATS lobectomy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Only eight studies reported a follow-up (6 months-2 years). The majority of cases were described in the eastern part of the world [15,18,19,21,22,[24][25][26][28][29][30][31]33,34]. Surprisingly, the presence of as many as three such cases was observed in Szczecin, in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The complex anatomy in SIT is a difficulty in the preoperative planning of thoracic procedures. Therefore, 3D-CT images were described in several included articles [28,29,33,34]. It is important to remember potential metastasis.…”
Section: Discussionmentioning
confidence: 99%